2020
DOI: 10.5194/essd-12-41-2020
|View full text |Cite
|
Sign up to set email alerts
|

Cloud_cci Advanced Very High Resolution Radiometer post meridiem (AVHRR-PM) dataset version 3: 35-year climatology of global cloud and radiation properties

Abstract: Abstract. We present version 3 of the Cloud_cci Advanced Very High Resolution Radiometer post meridiem (AVHRR-PM) dataset, which contains a comprehensive set of cloud and radiative flux properties on a global scale covering the period of 1982 to 2016. The properties were retrieved from AVHRR measurements recorded by the afternoon (post meridiem – PM) satellites of the National Oceanic and Atmospheric Administration (NOAA) Polar Operational Environmental Satellite (POES) missions. The cloud properties in versio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 36 publications
0
73
0
1
Order By: Relevance
“…Cloud optical (thickness, effective radius, water path) and thermal (cloud top temperature and pressure) properties are retrieved from ORAC using an optimal estimation-based approach. These retrievals and reanalysis profiles of temperature, humidity and ozone are then ingested into BUGSrad, a two-stream correlated-k broadband flux algorithm (Stephens et al, 2001) that outputs the fluxes at the top and bottom of the atmosphere and is shown to have excellent agreement when applied to both active (CloudSat) and passive (Advanced Along Track Scanning Radiometer) satellite sensors compared to the Clouds and the Earth's Radiant Energy System (Henderson et al, 2013;Stengel et al, 2020). In addition, offline radiative transfer sensitivity tests using vertical profiles from our model were conducted with BUGSrad to identify the source of the differences in fluxes between clean and polluted conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Cloud optical (thickness, effective radius, water path) and thermal (cloud top temperature and pressure) properties are retrieved from ORAC using an optimal estimation-based approach. These retrievals and reanalysis profiles of temperature, humidity and ozone are then ingested into BUGSrad, a two-stream correlated-k broadband flux algorithm (Stephens et al, 2001) that outputs the fluxes at the top and bottom of the atmosphere and is shown to have excellent agreement when applied to both active (CloudSat) and passive (Advanced Along Track Scanning Radiometer) satellite sensors compared to the Clouds and the Earth's Radiant Energy System (Henderson et al, 2013;Stengel et al, 2020). In addition, offline radiative transfer sensitivity tests using vertical profiles from our model were conducted with BUGSrad to identify the source of the differences in fluxes between clean and polluted conditions.…”
Section: Methodsmentioning
confidence: 99%
“…For AVHRR datasets retrieving liquid while CALIOP retrieving ice, CLARA-A2 revealed more cases than Cloud_cci v2 and v3 for temperatures below −30°C and down to −41°C; For this reason, CLARA-A2 shows SLF around 7% between −40°C and −41°C using the collocated data ( Figure 1a) and around 17% using the noncollocated data (Figure 1b). A quantitative analysis of the differences between CALIOP and Cloud_cci v2 and v3 can be found in Stengel et al (2020): While any phase bias of Cloud_cci v2 and v3 with respect to CALIOP has nearly vanished for COTs of ∼0.15 into the clouds, there is still a significant bias at COT = 1 for the Cloud Top Height (CTH) of ice clouds, to which CTT is linked. As a consequence, CTH is usually retrieved from levels below the levels used to retrieve the phase, so that the retrieved CTT can be warmer than the effective temperature of the assigned cloud top phase, agreeing to our results.…”
Section: Resultsmentioning
confidence: 99%
“…The datasets we analyze are Cloud_cci AVHRR‐PMv2 (Stengel et al., 2017), Cloud_cci AVHRR‐PMv3 (Stengel et al., 2020), CLARA‐A2 (Karlsson et al., 2017), and CALIOP V4 (Liu et al., 2019). While the first three are based on the polar‐orbiting passive satellite sensor AVHRR onboard NOAA satellites, CALIOP is an active sensor onboard the polar‐orbiting CALIPSO satellite and is part of the NASA A‐Train.…”
Section: Datasets and Methodsmentioning
confidence: 99%
“…Thus, in general, the Naïve Bayesian method produces reasonably good results, but some defects are unavoidable. Consequently, future developments should aim to introduce true Bayesian approaches (e.g., as suggested in [36,37]) or more advanced machine learning methods (e.g., as suggested in [10,38]). However, it is imperative to use the principles from this study to ensure that the different conditions for cloud detection over different Earth surfaces are taken into account for such approaches as well.…”
Section: Limitations Of the Naïve Bayesian Methodsmentioning
confidence: 99%
“…Examples of this are given in [1][2][3][4][5], providing climate monitoring applications based on real-time or near-real-time cloud screening methods. Some schemes introduce increased flexibility [6][7][8][9][10], but no method focuses exclusively on the climate monitoring task. In this paper, we address the disadvantages associated with using similar methods in both real-time and climate monitoring applications.…”
Section: Introductionmentioning
confidence: 99%